1990
DOI: 10.1037/0022-3514.59.4.743
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of parental divorce on optimism and trust: Changes in general assumptions or narrow beliefs?

Abstract: Two studies were conducted to examine the long-term impact of parental divorce on beliefs about the self and others. In Study 1, college-aged children of divorce and students from intact families did not differ on 8 basic assumptions or on measures of depression. Those whose parents had divorced, however, were less optimistic about the success of their own future marriages. Assumptions about the benevolence of people best predicted the marital optimism of the parental divorce group, but not of the intact famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 32 publications
(74 reference statements)
1
65
0
3
Order By: Relevance
“…<…> Особенности происхождения и личностные черты, привнесенные супругами в брак, также влияют на адаптивные процессы. Например, самоотчеты супругов об их детстве в родительской семье связаны с массой специфических жалоб на их соб-ственный брак [Overall, Henry, Woodward, 1974] и на отношение к институту брака в целом [Franklin, Janoff-Bulman, Roberts, 1990]. Исследования жизненного пути (индивида), которые проводились в течение более чем 20 лет, выявили, что дети из дистрессовых или распавшихся браков имеют более низкие социальные навы-ки как взрослые [Franz, McCleland, Weinberger, 1991;Koestner, Franz, Weinberger, 1990].…”
Section: гипотезы и результаты исследованияunclassified
“…<…> Особенности происхождения и личностные черты, привнесенные супругами в брак, также влияют на адаптивные процессы. Например, самоотчеты супругов об их детстве в родительской семье связаны с массой специфических жалоб на их соб-ственный брак [Overall, Henry, Woodward, 1974] и на отношение к институту брака в целом [Franklin, Janoff-Bulman, Roberts, 1990]. Исследования жизненного пути (индивида), которые проводились в течение более чем 20 лет, выявили, что дети из дистрессовых или распавшихся браков имеют более низкие социальные навы-ки как взрослые [Franz, McCleland, Weinberger, 1991;Koestner, Franz, Weinberger, 1990].…”
Section: гипотезы и результаты исследованияunclassified
“…Other researchers found that children who have experienced parental divorce were pessimistic about their future relationship outcomes with their partners and that these pessimistic views were tied to their assumptions about people and their lack of benevolence. In addition to the aforementioned inding, the same researchers found that trust beliefs of these children were diminished when they experienced continuous conlicts within their families [8].…”
Section: Sufering and Prosocial Orientationmentioning
confidence: 99%
“…Beyond direct associations with psychopathology, it was posited that some individuals who had a brush with adversity develop negative perceptions of people and the environment around them. While those who are free from past trauma tend to hold beliefs that the world is just, meaningful, and benevolent, those who were exposed to adverse life events often exhibit a diminished belief in a benevolent or meaningful world characterized by virtue [8]. In one instance, Poulin [9] found that exposure to violence-related events predicted subsequent decrease in benevolence beliefs.…”
Section: Sufering and Prosocial Orientationmentioning
confidence: 99%
“…Alesina and La Ferrara (2002) suggest that divorce or separation can significantly decrease interpersonal trust levels, using cross-sectional data from the US between 1974 and 1994 (also see Franklin et al, 1990, or King, 2002, in that regard). However, in our panel data estimation including individual-level fixed effects none of the derived coefficients turns statistically significant on conventional levels.…”
Section: Other Major Life Eventsmentioning
confidence: 99%